Investigation on tolerance of Metarhizium flavoviride Ma130821 to environmental stress factors and responses on biological control of larvae of Potosia brevitarsis Lewis. Issue 11 (21st November 2022) - Liu, Si‐Yu; Lai, You‐Peng; Du, Guang‐Zu; Chen, Bin
Abstract: Entomopathogenic fungi of Metarhizium spp ., are one of the candidates for eco‐friendly pest control instead of chemical control agents. But the development involved in producing a wide range of mycoinsecticides and application of biotechnology widely is restricted, usually due to the defect of slow action and sensitivity to environmental stresses. This study evaluates the tolerance of conidia of Metarhizium flavoviride Ma130821 to high temperature exposure, humidity level, ultraviolet radiation and the pathogenicity against larvae of Potosia brevitarsis Lewis under environmental stresses. Results showed that M. flavoviride Ma130821 had the higher tolerance ability to 40°C with continuous exposure for 24 h, the conidial germination rate was 54.00%, radial growth was 1.59 mm/day and sporulation was 9.37 × 10 6 conidia/cm 2, the ability to desiccation with humidity of 53% (85.33%, 1.94 mm/d, 2.13 × 10 7 conidia/cm 2 ), the ability of uvioresistant effect with 900 s radiation (98.11%, 0.91 mm/d, 8.87 × 10 6 conidia/cm 2 ). The data of bioassay at artificial adverse condition had been fitted to the time–concentration–mortality (TCM) model. The cumulative mortality of P. brevitarsis larvae was 76.67% with conidial concentrations of 3.41 × 10 8 conidia/mL. The low lethal concentration (LC50 ) in 7 days after inoculation (DAI) and short lethal time (LT50 ) was 6.70 × 10 9 conidia/mL and 8.02 days, respectively. The mortality also reached to 73.33% at natural condition, with conidial concentration of 3.75 × 10 8 conidia/mL, but the LT50 delayed to 14.08 days. Our results demonstrate that entomopathogenic fungi M. flavoviride Ma130821, with significantly and superior antistress capacity and high virulence, could be considered a promising biocontrol agent against white grubs.